STRATEGI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL DALAM MEWUJUDKAN TERTIB ADMINISTRASI KEPENDUDUKAN DI KOTA PONTIANAK - Mega Adelika E.42009081 Adelika E.42009081 (FISIP Universitas Tanjungpura Pontianak, 2021)
Dinas Kependudukan dan Pencatatan Sipil Kota Pontianak is a Regional Working Unit (SKPD) that has a job in strightening demography administration in Pontianak city. One of the documents that published are Family Card (KK). According to the problems that faced by this department which are fragmentary of regulation of KK-making, delays of reporting, delays of publishing time and double data, the researcher wants to describe and analyze the strategy of Dinas Kependudukan dan Pencatatan Sipil in realizing the KK administration order in Kota Pontianak. This research is using descriptive research, with qualitative approach. Subject of this research is Civil Servant of Dinas Kependudukan dan Pencatatan Sipil which is hierarchily take control in making KK and some Ketua RT. The strategy observed based on Tangkilisan concept which is management of organization resources and organization interaction towards environment.According to the result of this research, the increase of organization resources management and organizational interaction towards environment to reach the real aim is needed. The researcher suggests to the related department to improve their way in managing organization resources that still far from optimum. Then, the most of all is doing innovations in interacting to society. Keywords : KK, Strategy, Organization Resources Management, Organizational Interaction